HUBUNGAN INDEKS MASSA TUBUH (IMT) TERHADAP DAYA TAHAN SISWA EKSTRAKURIKULER BOLA VOLI DI SMP NEGERI 1 SIAK HULU - Novi Dianah Indah Nur Rohmah; Agus Sulastio; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this research was to determine the correlation Body Mass Index (BMI) and the endurance of volleyball extracurricular students at SMP Negeri 1 Siak Hulu. This type of research uses the correlation method with a quantitative approach, namely the method used to present the results of research using statistics. The sample subjects taken in this study were 12 students consisting of 6 male students and 6 female students who took part in volleyball extracurricular at SMP Negeri 1 Siak Hulu which were taken from 25 student population using purpusive sampling technique. The results of data analysis show that there is a correlation Body Mass Index (BMI) and the endurance of volleyball extracurricular students at SMP Negeri 1 Siak Hulu of -0.268 which is in the range of 0.20 – 0.40, which means that there is a correlation variable X and Variable Y weak or low.Key Words: Body Mass Index, Endurance, Volleyball.